CT-Guided Percutaneous Fine Needle Aspiration Cytology of Pulmonary Mass. - Shahi, Rajive Raj; Shrestha, Mukunda Singh; Pant, Sujata; Singh, Sunil; Maharjan, Dinesh (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Following the first study of Computed tomography guided trans thoracic biopsy of lung lesion by Haaga and Alfidi in 1976, CT guided transthoracic biopsy has been widely used for confirming the diagnosis of suspicious lung lesions. This study is aimed to assess the effectiveness of Transthoracic percutaneous fi ne needle aspiration cytology and frequency of associated complications. Methods: A retrospective, hospital based study was performed between 11/06/2008 and 1/12/2009 at Department of Radiology, Shree Birendra Hospital, Kathmandu, Nepal. Thirty nine consecutive cases of lung lesions who underwent Trans Thoracic Percutaneous Fine Needle Aspiration Cytology (TTFNAC) under CT guidance were analysed. Smears of the aspirated material were evaluated by the pathology consultant (cytopathological evaluation) for adequacy. Results: There was adequate material for a cytopathological diagnosis in thirty four (87.18 %) cases. Two cases were hemorrhagic while three cases revealed only reactive cells thus inadequate and non representative case constituted (12.8 %). Eight cases were reported as benign (23.53 %). Twenty three samples (67.65%) were reported as definite malignant cases and three cases (8.82%) showed atypical cells, suggestive of malignancy. Squamous cell carcinoma was the single most frequent histological diagnosis (12 cases). Conclusions: The FNAC of lung is useful, safe and economical technique providing 87% diagnostic accuracy for lung mass without significant increase in complications. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/37-41 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7766